Kvinnotidningar: Hertha - Språkbanken Text (University of Gothenburg, 2024)
A corpus with texts from the women's newspaper Hertha

En korpus med texter från kvinnotidningen Hertha, tidskrift för den svenska kvinnorörelsen - utgiven av Fredrika-Bremer-Förbundet
Kvinnotidningar: Hertha
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik